Leukotriene B4 type‐1 receptor signaling promotes liver repair after hepatic ischemia/reperfusion injury through the enhancement of macrophage recruitment. Issue 8 (29th April 2013) - Ohkubo, Hirotoki; Ito, Yoshiya; Minamino, Tsutomu; Mishima, Toshiaki; Hirata, Mitsuhiro; Hosono, Kanako; Shibuya, Masabumi; Yokomizo, Takehiko; Shimizu, Takao; Watanabe, Masahiko; Majima, Masataka
Abstract : Recruited macrophages play a critical role in liver repair after acute liver injury. Leukotriene B4 (LTB4 ) is a potent chemoattractant for macrophages. In this study, we investigated the role of LTB4 receptor type 1 (BLT1 ) in liver repair during hepatic ischemia/reperfusion (I/R) injury. BLT1‐knockout mice (BLT1 ‐/‐ ) or their wild‐type counterparts (WT) were subjected to partial hepatic I/R. Compared with WT, BLT1 ‐/‐ exhibited delayed liver repair and hepatocyte proliferation accompanied by a 70% reduction in the recruitment of macrophages and a 70–80% attenuation in hepatic expression of epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), and VEGF receptor 1 (VEGFR1). Disruption of BLT1 signaling also reduced the expression of EGF by 67% on recruited macrophages expressing VEGFR1 in the injured liver. Treatment of WT mice with an EGF‐neutralizing antibody delayed liver repair and reduced macrophage recruitment, compared with control immunoglobulin G (IgG). BLT1 signaling enhanced the expression of VEGF, VEGFR1, and EGF in isolated peritoneal macrophages in vitro. These results indicate that BLT1 signaling plays a role in liver repair after hepatic I/R through enhanced expression of EGF in recruited macrophages and that the development of a specific agonist for BLT1 could be useful for liver recovery from acute liver injury.—Ohkubo, H., Ito, Y., Minamino, T., Mishima, T., Hirata, M., Hosono, K., Shibuya, M., Yokomizo, T., Shimizu, T., Watanabe, M., Majima, M., Leukotriene B4 type‐1 receptor signaling promotes liver repair after hepatic ischemia/reperfusion injury through the enhancement of macrophage recruitment. FASEB J. 27, 3132–3143 (2013). www.fasebj.org